In silico design of 2D polymers containing truxene-based platforms: insights into their structural and electronic properties - Gámez-Valenzuela, Sergio; Echeverri, Marcelo; Gómez-Lor, Berta; Martínez, Jose I.; Ruiz-Delgado, María del Carmen (The Royal Society of Chemistry, 2020)
In the present work, we investigate two-dimensional (2D) conjugated polymers based on C3-symmetric truxene-based cores at the density functional theory (DFT) level. In total, 27 different 2D polymers have been exhaustively studied with the aim to explore the impact of the following effects on the electronic and charge-transport properties: (i) the nature of the conjugated platform, going from electron-rich truxene (Tx) and triindole (Tr) units to electron-deficient truxenone (To) cores, (ii) the spacing of the cores with different bridges, i.e., phenylene (Ph) or ethynylene (A) units, (iii) the linker position (2,7,12-substitution in the T2 polymers and 3,8,13-substitution in T3 polymers), and (iv) the increased number of p-bridges connecting the cores, from three linkers in T2 and T3 to six linkers in T2,3. To this end, we have carried out a large battery of DFT calculations on fragments extracted from the 2D polymers (dimers and trimers) as well as on the corresponding periodic 2D structures (infinite monolayers and self-assembled monolayers) using periodic boundary conditions. Our results show that simultaneous manipulation of the pore surface size and band-gap engineering together with charge- transport parameters can be achieved in these truxene-based 2D polymers by fine-tuning their structural features. The contributions of this study to the overall understanding of the structure–electronic property relationships of these semiconducting polymers and its correlation with available experimental work are highlighted. Our results provide interesting guidelines to design novel 2D materials with applications ranging from sensing to photocatalysis or electronics.
Keywords: 2D polymers; DFT calculations; In silico design; Organic electronics